Utilization of Plasma Technology to Control Weed Seed Germination - Bukhori, Anwar; Guntoro, Dwi; Sudradjat; Tri Sugiarto, Anto (Journal of Tropical Crop Science, 2024)
Efforts to reduce herbicide use include employing cold plasma technology, which produces heat energy from UV plasma rays using a combination of electrical power. This research aimed to determine the effectiveness of plasma technology in controlling weeds and to identify the optimal voltage and duration for using cold plasma technology to inhibit seed germination. The study was conducted at the Ecotoxicology Laboratory and Seed Propagation Laboratory of IPB in Bogor, Indonesia, from January to March 2023. It comprised two experiments: (1) testing the voltage and time duration of cold plasma technology and (2) examining the effect of electrode needle distance on mustard seeds. The first experiment followed a completely randomized design with plasma voltage and time duration as the treatments. The second experiment used a single-factor completely randomized design to investigate the electrode needle distance. Each experiment included four replications. The results indicated that a voltage of 140 kV with a duration of 80 seconds could suppress mustard seed germination by up to 100%. Additionally, using an electrode needle distance of 0.5 cm reduced the germination percentage of mustard seeds by up to 100% at 7 and 14 days after treatment.